THE ROLE OF INTERCULTURAL COMMUNICATION IN DIPLOMATIC RELATIONS (Ustozlar uchun, 2026)
Intercultural communication plays a critical role in diplomatic relations, enabling diplomats to navigate the complexities of international interaction in a culturally diverse world. Diplomats frequently engage with representatives from different linguistic, social, and cultural backgrounds. Understanding cultural norms, communication styles, and nonverbal cues allows diplomats to build trust, prevent misunderstandings, and promote effective international cooperation. This study examines the significance of intercultural communication in modern diplomacy, emphasizing its role in negotiation, conflict resolution, and international collaboration. The research demonstrates that cultural competence is an essential skill for diplomats, interpreters, and international communication specialists in fostering positive and sustainable diplomatic relations.